Global research on underutilized crops: An assessment of current activities and proposals for enhanced cooperation - Williams, J.T.; Haq, N.; International Centre for Underutilized Crops (2002)
This report has been produced to provide a succinct overview of the global research activities on underutilized crops. It is aimed at policy-makers, funding agencies and research administrators but it is hoped that it will also be of use to the scientific community. The report results from a request from a workshop convened by the Genetic Resources Policy Committee for the Consultative Group on International Agricultural Research. The workshop was held at the M.S.S. Research Foundation, Chennai, India in 1999. It will be seen that the number of countries with dedicated research programmes on underutilized crops is very small. Much of the current activity is carried out through networking arrangements. An analysis suggests that there is a need to re-think the current networks and a strategy for expanded research cooperation should include due attention to information and enhancing research priority setting and cooperative research.